Devés-Valdés, Eduardo. PENSAMENTO PERIFÉRICO. UMA TESE INTERPRETATIVA GLOBAL. Idea – Usach, 2012. 1.050p. Disponível em: www.eduardodevesvaldes.cl. - Bernardo, Horacio (Revista Direito em Debate, 2013)